Great Writing 3 : From Great paragraphs to Great Essays - Folse, Keith S. (National Geographic learning, 2015)
Now with engaging National Geographic images, the new edition of the Great Writing series helps students write better sentences, paragraphs, and essays. The new Foundations level meets the needs of low-level learners through practice in basic grammar, vocabulary, and spelling, while all levels feature clear explanations, student writing models, and meaningful practice opportunities. The new edition of the Great Writing series is the perfect writing solution for all learners from beginning to advanced.